1974
DOI: 10.2135/cropsci1974.0011183x001400050009x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tannin on In Vitro Dry Matter and Protein Disappearance in Sorghum Grain1

Abstract: The purpose of this investigation was to determine the effect of tannin and added urea on in vitro dry matter disappearance (IVDMD) and in vitro protein disappearance (IVPD) in sorghum (Sorghum bicolor (L.) Moench) grain. IVDMD of low and high tannin genotypes after 48 hours of fermentation was 72.5 and 46.4% respectively. The addition of urea increased IVDMD to 93.4 and 79.2% for the low and high tannin genotypes. IVPD of low and high tannin genotypes was not affected by urea and averaged 88.2 and 69.6%, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

1977
1977
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 1 publication
1
11
0
1
Order By: Relevance
“…Digestion of barley and wheat is more rapid than that of corn or sorghum because of the natural abundance of proteins of low digestibility (eg prolamins) in the vitreous (horny) endosperm of the latter 28. In addition, the presence of polyphenols in some cereals, including sorghum, is believed to contribute to the higher resistance of those grains to ruminal hydrolysis 29…”
Section: Discussionmentioning
confidence: 99%
“…Digestion of barley and wheat is more rapid than that of corn or sorghum because of the natural abundance of proteins of low digestibility (eg prolamins) in the vitreous (horny) endosperm of the latter 28. In addition, the presence of polyphenols in some cereals, including sorghum, is believed to contribute to the higher resistance of those grains to ruminal hydrolysis 29…”
Section: Discussionmentioning
confidence: 99%
“…The antinutritional properties of tannins are well documented from numerous in vitro (Schaffert et al 1974;Ramachandra et al 1977;Chibber et al 1980;Horigome et al 1988;Garrido et al 1989), and in vivo (Cousins et al 1981;Horigome et al 1988;Ahmed et al 199 1) studies, which showed reduced digestibility of protein in diets containing tannins. Many experiments have shown that tannins in the diet result in reduced weight gain and poor feed efficiencies in chicks (Armstrong et al 1974;Ahmed et al 1991), rats (Featherston & Rogler, 1975;Elkin et al 1990;Mole et al 1990) and pigs (Pathak & Ranjahan, 1973;Cousins et al 1981;Mitaru et al 1984).…”
mentioning
confidence: 98%
“…It may also affect digestibility values (Harris, 1971) and decrease protein utilization, due to reduced amino acid availability (Schaffert, Lechtenberg, Oswalt, Axtell, Pichett and Rhykerd, 1974). In the present trial, palatability was not adversely affected to the extent that it prevented consumption of the full allowances offered according to the restricted feeding scale.…”
mentioning
confidence: 55%